Association of Polymorphism of Arginine-Vasopressin Receptor 1A (AVPR1a) Gene With Trust and Reciprocity - Nishina, Kuniyuki; Takagishi, Haruto; Takahashi, Hidehiko; Sakagami, Masamichi; Inoue-Murayama, Miho (Frontiers in Human Neuroscience, 2019)
Oxytocin is known to play an important role in trust, whereas the involvement of other peptide hormones has not been evaluated. In this study, we focused on microsatellite polymorphisms in the intron of the arginine-vasopressin receptor 1a (AVPR1a) gene and examined whether the association between the repeat lengths in the intron of AVPR1a is associated with trust and reciprocity in humans. Four hundred and thirty-three participants played the trust game, answered the attitudinal trust question, and their buccal cells were collected. Results showed that men with a short form of AVPR1a tend to send more money to the opponent, even if there is a possibility of being betrayed by the opponent. Additionally, people with a short form of AVPR1a tended to return money to the opponent who trusts them. However, attitudinal trust was not associated with AVPR1a. These results indicate that arginine-vasopressin receptor 1a plays an important role in trust and reciprocal behaviors.